Efectos de la fertilización edáfica interaccionada con foliares a base de algas marinas, sobre el desarrollo y rendimiento del cultivo de maíz (Zea mays L.), en la zona de Montalvo - Jiménez Arias, Linda Esperanza (2020)
The research was carried out on the premises of the La Esperanza estate, in the La Guadalupe Campus of the Montalvo canton, in the province of Los Ríos. The Emblema maize hybrid was investigated, using three levels of soil fertilization, two sources of biostimulants and two doses for each source, in three replications. The objective of the work was to evaluate the application of the most biostimulant soil fertilization levels in corn production. Corn sowing was done manually in 20 m2 experimental plots. The treatments were distributed in an AXB factorial design. The andeva determined the statistical significance and evaluation of means was performed with the Tukey significance test at 5 %. The variables evaluated were: plant height, insertion height, days to flowering, days to harvest, ears diameter, ears length, grain-tuza ratio, grain weight, yield per hectare and economic analysis. The results show a greater increase in grain with the use of 161 N - 69 P - 90 K - 48 S kg/ha as a fertilization program, while between the biostimulants and the doses applied we did not achieve marked differences between them. The most outstanding interaction in almost all the variables evaluated was 161 N - 69 P - 90 K - 48 S kg / ha plus Ascophyllum nodosum 1,0 L/ha and maximum Ecklonia 1,0 L/ha, the same ones that even the higher production averages. Statistical significance was not evidenced in the variables days to flowering, days to harvest and number of ears per plant.